Equilibrium solubility, inter- and intra-molecular interactions and solvation performance of flutamide in some aqueous blended co-solvents. (December 2021) - Li, Yanxun; Li, Congcong; Gao, Xiaoqiang; Wan, Yameng; Lv, Hekun
Graphical abstract: Highlights: Flutamide solubility in four aqueous solutions was determined and correlated. Solubility profile was illustrated by partial Hansen solubility parameter. Solvent effect was studied by KAT-LSER model. Solvation behavior was studied via IKBI and EHSA method. Abstract: The current research was devoted to the solubility profile and its computational methodologies, partial Hansen solubility parameter, inter- and intra-molecular interactions, and solvation performance for the systems formed by crystalline flutamide dissolved in water and cosolvent, i.e . ethanol/isopropanol/acetonitrile/1, 4-dioxane. All solubility experimentations were done via a common shake-flask saturation method at a pressure of atmosphere ( p = 101.2 kPa) and the temperature range from 278.15 to 323.15 K. The solubility in magnitudes of flutamide were recorded as the lowest in pure water at 278.15 K; and the highest in pure co-solvent at 323.15 K. The three-dimensional Hansen solubility parameters were utilized here to illustrate the solubility profile. The quantifiable explanation of solvent effect was carried out via modelling the flutamide solubility using linear solvation energy relationships. Satisfactory outcomes for correlating the solubility magnitudes were realized by means of modified van't Hoff–Jouyban–Acree, modified Wilson and Jouyban–Acree models with the relative average errors of < 6. 67 %. The observed solubility data at 298.15 K were further studied by the extended Hildebrand solubility approach, acquiring the relative average deviations of < 1.54 %. The preferential solvation investigation of flutamide was further performed through quantitation by inverse Kirkwood–Buff integrals. The positive values of preferential solvation parameters in co-solvent-rich and middle composition blends point to that the drug flutamide is preferentially solvated by the co-solvent. In these composition ranges, flutamide is possibly acting as Lewis acid performance with 1, 4-dioxane/ethanol/isopropanol molecules; while for the aqueous acetonitrile solutions, the solvation behavior is responsible for the polarization effect.